Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/ctpp.201700147
|View full text |Cite
|
Sign up to set email alerts
|

Resonant and anti‐resonant modes of the dilute, spin‐inbalanced, two‐dimensional electron liquid including correlations

Abstract: A spin‐sensitive linear response theory is presented that includes correlations beyond the well‐known random phase approximation. Especially for very dilute systems, such correlations play an important role. The response functions obtained give insight into both charge and longitudinal magnetic excitations. In addition to the spin‐plasmon, we propose a new regime where no magnetic excitation is possible, namely the magnetic anti‐resonance. Both effects lie in experimentally accessible ranges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Another crucial feature of partially polarised 2DELs are lines ω(q), where the system ignores external stimulation ("anti-resonances") [26,45]. Along ω mAR (q) it cannot be excited by a magnetic field; similarly, for ω vAR (q) external stress variations cause no response.…”
Section: Resonances and Anti-resonances -mentioning
confidence: 99%
See 2 more Smart Citations
“…Another crucial feature of partially polarised 2DELs are lines ω(q), where the system ignores external stimulation ("anti-resonances") [26,45]. Along ω mAR (q) it cannot be excited by a magnetic field; similarly, for ω vAR (q) external stress variations cause no response.…”
Section: Resonances and Anti-resonances -mentioning
confidence: 99%
“…Plasmon pole approximation. In order to deepen the understanding of the physics behind these new modes and anti-resonances, the plasmon pole approximation (PPA) (also single-mode or Bijl-Feynman approximation) [1] suits best [26]. We briefly outline it for the spin-and valley-sensitive case.…”
Section: Resonances and Anti-resonances -mentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results are shown in Table 1. According to Tendero et al, [72] the plasma temperature varies from 0.67 eV (plasma envelop) to 1.36 eV (plasma core), which enables high-temperature applications (the use of the thermal effect of the plasma). [67] In addition, an increase in the excitation temperature with the increase in the number of pulses was observed.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…Nemcova et al [70] and Run Liu et al [71] have suggested that a ceramic film can be formed due to increased heating from the larger discharges, leading to more extensive melting of the coating during the arc process. According to Tendero et al, [72] the plasma temperature varies from 0.67 eV (plasma envelop) to 1.36 eV (plasma core), which enables high-temperature applications (the use of the thermal effect of the plasma). The melting and boiling points of WC are 2942 and 6203 K, respectively.…”
Section: Spectroscopic Analysismentioning
confidence: 99%